SEMANTIK AL-QUR’AN (PENDEKATAN SEMANTIK AL-QUR’AN THOSHIHIKO IZUTZU) - Derhana Bulan (Institut Agama Islam Negeri (IAIN) Manado, 2019)
Al-Qur'an as a text (signs) of the holy book, can always be interpreted and the opportunity is always open to be studied and thought about the meaning of the verses, according to its position as